Large Endometrioma That Triggered a Hypertensive Emergency: A Case Report - Varnita Vishwanath; Gregory Marchand; Ali Azadi (Hindawi Limited, 2024)
Endometriosis is a common gynecological condition in women of reproductive age and has variable symptomology such as pelvic pain, menorrhagia, dysmenorrhea, dyspareunia, and infertility. Endometriomas are a form of endometriosis and are characterized by cystic masses most commonly found on the ovaries. This case discusses the management of a rare occurrence of a 25-cm endometrioma in a patient without a prior diagnosis of endometriosis, who presented to the emergency room in an acute hypertensive emergency. It is believed that the large cyst caused a mass effect against renal vasculature precipitating renovascular hypertension that required immediate intervention. This case was approached with minimally invasive surgical removal of the cyst and lysis of adhesions without postoperative complications.